Regulatory challenges affecting the adoption of uncrewed aircraft systems in agriculture - Schrader, Spencer Ryan (My University, 2025)
In August of 2016, the Federal Aviation Administration (FAA) released regulations for Small Uncrewed Aircraft Systems (sUAS), or drones, operating in a commercial manner. These regulations (Part 107) allowed for the widespread adoption of drones weighing less than 55 pounds for countless industries. One use that many are still hopeful will adopt drone technology is agriculture, specifically for crop spraying. However, since the majority of aerial applicating drones fall outside of the weight restriction of Part 107, this particular use hasn’t quite taken off as expected because of the regulatory framework for drones weighing 55 pounds or larger. This paper focuses on the processes that the FAA took for developing and releasing Part 107 and outlines what the future could look like for commercial drones that fall outside of that regulatory environment, including drones used for aerial applicating. Additionally, this paper will discuss general views of farmers in Kansas on the use of drone technology in agriculture and how that affects adoption rate. Finally, this paper will consider the types of drones available on the commercial market today as well as how other countries are using them for agricultural purposes.
Keywords: UAS; Drone; Aerial application; Agriculture; FAA; Crop spraying